Abusers of Land Value Zone Utilization: Study of Special Funds and D.I.Yogyakarta Tourist Visitors - Davy, Leng; Saleh, Rahmat (JAMPE (Journal of Asset Management and Public Economy), 2024)
The purpose of this research is to identify the effect of special funds and tourist visits on the number of tours in land value zones in D.I. Yogyakarta Province. The research adopts a panel data approach, utilizing secondary data from government agencies in the research location. Data collection employs a non-probability purposive sampling model, incorporating a total of 30 observational data points representing 5 districts and cities in D.I. Yogyakarta Province. Data analysis is conducted through panel data regression using the Eviews 12 SV analysis tool. The results of this research indicate that the best model chosen is the fixed effect model. The research data statistically confirm the normal distribution of data observations. Specifically, the findings reveal that the number of tourist visits has a significant and positive effect on land value zones in D.I. Yogyakarta Province. However, the variable of special funds does not exhibit any significant effect on these zones. The contribution of this study is in providing insights into the factors influencing land value zones in the province, particularly the noteworthy positive impact of tourist visits. This understanding can be valuable for policymakers and stakeholders in formulating strategies to enhance land value and promote sustainable tourism development in the region.